Blockchain Sebagai Fondasi Transformasi Keuangan Sektor Kesehatan: Systematic Literature Review - Sisi Maghfirah Rahmah Sembiring; Muhammad Simba Sembiring; Muhammad Nur Maghribi Sembiring (Journal of Innovative and Creativity, 2026)
Financial management in Indonesia's health sector still faces challenges in the form of low transparency, administrative inefficiency, and high risk of fraud in the claims and financing system. Blockchain technology offers a solution through a secure, transparent, and immutable decentralised recording system. This study aims to systematically examine the implementation of blockchain in supporting the health sector financial system and to identify the benefits, challenges, and policy implications for Indonesia. The method used is a Systematic Literature Review (SLR) based on the Scopus, Web of Science, and IEEE Xplore databases. The results of the study show that blockchain has the potential to increase efficiency, accelerate the claims process, improve accountability, and reduce fraud through smart contracts and audit trails. However, its implementation is still limited to the conceptual stage and pilot projects, so policy support and a phased implementation strategy are needed.